Customer Relationship Management. Websites Analysis of the Top Ten Consumer Goods Companies - Alexandru Ioan Rîpa; Luminița NICOLESCU (Management Dynamics in the Knowledge Economy, 2023)
Customer relationship management (CRM) became one of the marketing practices that is assumed to bring success to companies in recent years. Therefore, the present research aims to identify the level of development of CRM in the top ten consumer goods companies as ranked at world level in 2021. Different models describe components of the CRM and the present research uses the theoretical framework proposed by Sin et al. (2005) that comprises four CRM dimensions: key customer focus, CRM organization, knowledge management and technology-based CRM. The methodology employed includes documentary research based on the public information available on the websites of the selected companies. Two types of analyses are conducted, descriptive analysis and comparative analysis. On overall, the dimension that is the most visible is the key customer focus, while the dimension that is the least visible is CRM organization. The results reveal that CRM is present in all top ten companies, but at different levels of development. US companies are more oriented towards CRM than companies originating from other countries. Companies that have a more developed CRM act in the direction of all four CRM dimensions.